2011
DOI: 10.1111/j.1538-7836.2011.04222.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum osteoprotegerin is a predictor for incident cardiovascular disease and mortality in a general population: the Tromsø Study

Abstract: To cite this article: Vik A, Mathiesen EB, Brox J, Wilsgaard T, Njølstad I, Jørgensen L, Hansen J.-B. Serum osteoprotegerin is a predictor for incident cardiovascular disease and mortality in a general population: the Tromsø Study. J Thromb Haemost 2011; 9: 638-44.Summary. Background: Osteoprotegerin (OPG) concentration in serum is associated with the presence and severity of atherosclerosis. Objective: To investigate the association between serum osteoprotegerin and the risk of a future myocardial infarction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 34 publications
5
65
1
2
Order By: Relevance
“…Previously, we observed an association between serum OPG and mortality from non-vascular causes in the general population (HR 1.31, 95% CI 1.22-1.41) (16). Similar risk estimates, although not statistical significant, for mortality from non-vascular events were reported from the Bruneck cohort study including 915 subjects from the general population (19).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Previously, we observed an association between serum OPG and mortality from non-vascular causes in the general population (HR 1.31, 95% CI 1.22-1.41) (16). Similar risk estimates, although not statistical significant, for mortality from non-vascular events were reported from the Bruneck cohort study including 915 subjects from the general population (19).…”
Section: Discussionsupporting
confidence: 82%
“…Recently, we reported that serum levels of OPG were associated with mortality of ischemic heart disease, stroke, and non-vascular causes (16). The latter finding may indicate that OPG is also a marker for other diseases as well as cardiovascular disease in the general population.…”
Section: Introductionmentioning
confidence: 88%
“…Therefore, biomarkers such as OPG that independently predict the decline in renal function over time may provide clinical utility for identifying patients with both poorer renal and cardiovascular clinical outcomes. The robust associations observed in our study with OPG and renal function at baseline, long-term renal decline at 5 and 10 years, rapid renal decline and renal disease-related hospitalizations and deaths, provides strong observational evidence that elevated OPG is an independent risk factor for CKD and may help explain the previous observations of others that elevated OPG is associated with CVD [23,25,26]. As a biomarker, OPG has several advantages, such as low intraindividual variation, it is present at relatively high serum levels and the detection is unaffected by freeze-thaw cycles [27].…”
Section: Discussionsupporting
confidence: 63%
“…1). Vik et al [19] followed 6265 subjects recruited from general population with a mean follow-up period of about 10.6 years and they found that increase in OPG level was associated with an increased future risk of myocardial infarction, total mortality, and mortality of ischemic heart disease independent of traditional cardiovascular risk factors. Similarly Pederson et al [4] reported increased risk of all-cause mortality, cardiovascular mortality and myocardial infarction with increasing OPG levels among patients with suspected stable angina, but independent effects were mainly confined to OPG levels above the 90 th percentile.…”
Section: Discussionmentioning
confidence: 99%